Ghana : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2003)
This report highlights Ghana's Poverty Reduction Strategy Paper (PRSP). The Ghana Poverty Reduction Strategy (GPRS) represents comprehensive policies, strategies, programs, and projects to support growth and poverty reduction from 2002 to 2004. The GPRS will also focus on providing the enabling environment that will empower all Ghanaians to participate in wealth creation and to partake in the wealth created. The GPRS aims at removing key obstacles to access and use, by the poor, of basic education, health care, population control, good drinking water, and improved sanitation.